SISTEM PAKAR KEHILANGAN PASOKAN LISTRIK PADA PT PLN (PERSERO) MENGGUNAKAN METODE INFERENSI BACKWARD CHAINING - Sari, Herlina Latipa; Sapri, Sapri (Jurnal Media Infotama, 2012)
An expert system is a computer software system that uses science, facts, and thinking in decision-making techniques to solve problems that normally can only be resolved by experts in the relevant field. in this case is the problem of the loss of the supply of electricity to PT PLN (Persero) Rayon Segara Bay.The loss of the number of power supplies sometimes occurs by two factors, namely technical and non-technical factors. This has encouraged the author in expert system development effort to detect the cause of the loss of power supplies that should be enjoyed by customers of PT PLN (Persero), the writer focuses on the number of customers who are in the Gulf region Rayon unit Segara. The research was conducted by studying the type of form loss, symptoms, causes and solutions to solve those problems. Then design and implement application programs into the software, to be used as a research tool, and test the correctness of the design results.The results of the study are electric supply loss expert system, which is designed using Visual Basic 6.0.Aplikasi can be used by an expert to make additions, changes and deletions of data, while users use it as a media consulting and obtaining information about the cause of the loss of supply electricity.